ANALISIS HASIL PENGUKURAN TINGGI TAKHIMETRI DENGAN SIPAT DATAR TELITI - Agnes Mulyani (UKI Press, 2020)
This study is to analyze the accuracy of height measurements using the Waterpass as high measurement of height and Kolida Theodolite DT 02. The location of the study was conducted in the Cawang Campus UKI area in November 2018. The method used is the measurement of the different height of polygon with a closed-loop by using Waterpass B2 and Kolida DT 02 Theodolite by using Tachymetri. Measurements are made three times with different loop, with the starting point and the end are the same point. The results showed that the calculation of the high closing error in rings 1, 2 and 3 with the Waterpass were 1 mm, 4 mm and 6 mm respectively. Whereas the high closing error with Theodolite Kolida DT 02 is12mm, 6mm, 19mm respectively. The Standard deviation of height difference with Waterpass is 1mm while with Theodolite 19mm. The conclusion that can be drawn is the Theodolite Kolida DT 02 can be used for high measurements in jobs that are not required to be very high accuracy. Keywords : Tachymetri:high measurement;accuracy